Revitalización de la memoria histórica sobre la toma de tierras en las comunidades: la Merced, Isinche de Alpamalag, cantón Pujilí provincia de Cotopaxi, compilación para los estudiantes de Décimo año de Educación General Básica. - Doicela Tigse, Luisa del Rocío (2014)
Pre-Inca, Inca, Colonial and Republican, we start from here to determine the origin of the communities in which there new laws and regulations for their existence in the first chapter, the forms of organization in each of the periods described. As the search for more varied diet for human societies as they were learning to domesticate animals and plants, and to use products of different ecological zones. Complex farming techniques were developed as agricultural terraces and irrigation canals. Narrate the struggles and clashes commoners to claim their identity and land, we argue about in possession and acquisition of land to the landowner, the description of the achievement of indigenous struggle projects. The pujilense case within the human values of our country is special and very novel , first , by the multifarious contribution of its people, and the latter because recent genealogical research has helped " discover" that many of the stars of our past were born in this wondrous land. The sociocultural aspect of the Communities from the worldview of the same detail how to maintain the culture and customs alive. The origin and establishment of communities of La Merced and Isinche Alpamalag are going small mountains,it so goes the description and narration of this valuable document.